2022
DOI: 10.3390/agronomy12112895
|View full text |Cite
|
Sign up to set email alerts
|

Early Season Growth Responses of Resistant and Susceptible Cotton Genotypes to Reniform Nematode and Soil Potassium Application

Abstract: A greenhouse study was conducted to investigate the roles that host plant resistance and soil potassium (K) levels play in affecting Rotylenchulus reniformis Linford and Oliveira (Tylenchida: Hoplolaimidae) (RN) populations and early season cotton (Gossypium hirsutum L.) growth. Two upland, RN-resistant cotton lines (G. barbadense introgressions: 08SS110-NE06.OP and 08SS100), a genetic standard (Deltapine 16) and a commercially available susceptible cultivar (PHY 490 W3FE) were evaluated at four different leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…The interaction of production practices, such as soil fertility, tillage, and cover crops, with reniform nematode reproduction and pathogenicity in cotton had varied results in the past literature (Asmus et al., 2008; Gazaway et al., 2000; Jones & McLean, 2004; Jones et al., 2006; Kularathna et al., 2014; Pettigrew et al., 2005; Reddy et al., 2006; Westphal & Smart, 2003). Recent greenhouse studies found no interaction of reniform nematode with major soil nutrients (nitrogen, phosphorus, and potassium) on early season growth or physiological characteristics of cotton (Singh et al., 2020; Singh, et al., 2022a, 2022b).…”
Section: Reniform Nematode Reproduction and Pathogenicity As Affected...mentioning
confidence: 99%
“…The interaction of production practices, such as soil fertility, tillage, and cover crops, with reniform nematode reproduction and pathogenicity in cotton had varied results in the past literature (Asmus et al., 2008; Gazaway et al., 2000; Jones & McLean, 2004; Jones et al., 2006; Kularathna et al., 2014; Pettigrew et al., 2005; Reddy et al., 2006; Westphal & Smart, 2003). Recent greenhouse studies found no interaction of reniform nematode with major soil nutrients (nitrogen, phosphorus, and potassium) on early season growth or physiological characteristics of cotton (Singh et al., 2020; Singh, et al., 2022a, 2022b).…”
Section: Reniform Nematode Reproduction and Pathogenicity As Affected...mentioning
confidence: 99%